2015
DOI: 10.1007/s11042-015-2935-4
|View full text |Cite
|
Sign up to set email alerts
|

Distant-talking accent recognition by combining GMM and DNN

Abstract: Recently, automatic accent recognition has been paid more and more attentions. However, there are few researches focusing on accent recognition in distant-talking environment which is very important for improving distant-talking speech recognition performance with non-native accents. In this paper, we apply Gaussian Mixture Models (GMM) and Deep Neural Network (DNN) to identify the speaker accent in reverberant environments. The combination of likelihood with these two approaches is also proposed. In reverbera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Additionally, LSTM was used in a hybrid emotion inference model that was proposed for inferring user emotion in a real-world voice-dialogue application, and a recurrent autoencoder was proposed to pre-train the LSTM to improve accuracy [32]. Further, GMM and DNNs were combined to identify distant accents in reverberant environments [26]. The authors found that this combination of classifiers outperformed the individual GMM and DNNs classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, LSTM was used in a hybrid emotion inference model that was proposed for inferring user emotion in a real-world voice-dialogue application, and a recurrent autoencoder was proposed to pre-train the LSTM to improve accuracy [32]. Further, GMM and DNNs were combined to identify distant accents in reverberant environments [26]. The authors found that this combination of classifiers outperformed the individual GMM and DNNs classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Although MP-aware DNN-based detection may provide a better performance than that of conventional DNN-based detection using only magnitude information, it may not work well due to the lack of feature-based resolution within low frequencies [17] and limited training data. In [18], a combination of GMM and DNN for distant-talking accent recognition was proposed to increase the accent recognition performance on limited training data. The result showed that the combination of these two different methods could improve the distant-accent recognition performance when compared to just an individual one.…”
Section: Proposed Combination Of Gmm and Mp-aware Dnnmentioning
confidence: 99%
“…The result showed that the combination of these two different methods could improve the distant-accent recognition performance when compared to just an individual one. Motivated by [18], a combination of CQCC-based GMM and MP-aware DNN was proposed to take advantage of these benefits of different classifications and features and was expected to achieve better performance. The probabilities obtained from the different systems are combined by the following equation.…”
Section: Proposed Combination Of Gmm and Mp-aware Dnnmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue, Ren et al [10] propose three integration schemes for robust distant-talking speech recognition which combine bottleneck feature extraction with dereverberation technique. As an accompanying paper by the same institution, Phapatanaburi et al [9] propose a combination of Gaussian Mixture Models (GMM) and Deep Neural Networks (DNNs) to identify the speaker accent in reverberant environments.…”
Section: Recognizing Humans and Understanding Their Behaviorsmentioning
confidence: 99%